Optimalisasi Restorative Justice dalam Penyelesaian Tindak Pidana Ringan: Pendekatan Humanis dalam Hukum Pidana - Alipio, M. Yosep; Haryadi, Slamet (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The Indonesian criminal justice system is still dominated by a retributive approach that focuses on punishment, even in handling minor crimes. This has led to overcrowded correctional facilities and a lack of effectiveness in achieving restorative justice. Restorative Justice (RJ) emerges as an alternative solution that prioritizes victim recovery, offender accountability, and community involvement in resolving cases. This study aims to analyze the implementation of RJ in resolving minor crimes, identify challenges in its application, and propose optimization strategies to enhance its effectiveness within Indonesia’s criminal justice system. Using a normative research method with a qualitative approach, this study examines existing legal regulations supporting RJ and explores case studies of its implementation in several regions. The findings indicate that RJ in minor crimes has been accommodated in several legal policies, such as Indonesian National Police Regulation No. 8 of 2021. However, obstacles remain, including limited understanding among law enforcement officials, a lack of public awareness, and the absence of comprehensive regulatory harmonization. Therefore, optimizing RJ requires strengthening legal policies, enhancing the capacity of law enforcement agencies, and increasing community participation in resolving disputes outside the formal judicial system. Effective RJ implementation is expected to create justice that focuses on restoration, reduce the burden on the criminal justice system, and ensure that law enforcement operates in a more humanistic and fair manner.